High-intensity ultrasound processing of baobab fruit pulp: Effect on quality, bioactive compounds, and inhibitory potential on the activity of α-amylase and α-glucosidase. (1st November 2021) - Ismail, Balarabe B.; Liu, Donghong; Pu, Yunfeng; He, Qiao; Guo, Mingming
Highlights: First report of the effect of high-intensity ultrasound (HIU) on baobab fruit pulp. HIU enhanced cloudiness and lowers 5-hydroxymethylfurfural than thermal processing. HIU increased the individual phenolic content and ascorbic acid retention. HIU significantly improved α-amylase and α-glucosidase inhibitions. HIU improvements were dependant on power intensity and time combinations. Abstract: Effect of high-intensity ultrasound (HIU) compared with thermal treatments on baobab fruit pulp (BFP) quality and bioactive properties were investigated. HIU treatments, particularly at intensities of 687.5 W/cm 2 for 5 min, and 344 W/cm 2 for 15 min significantly (p < 0.05) increased the cloudiness index, ascorbic acid (AA) retention, total phenolic and flavonoid contents, and antioxidant capacity besides a more potent α-amylase and α-glucosidase inhibition relative to thermally treated samples. Moreover, the physicochemical parameters, colour index, and browning index were maintained with HIU besides lower 5-hydroxymethylfurfural values than thermal processing. HPLC analysis revealed that the content of most phenolic compounds was the highest in HIU treatments besides a 235–256% increase in procyanidin C1 compared with control samples. The AA retention following HIU treatments was 87.62–102.86% compared to 30.47–61.90% in thermally treated samples. Our analyses portrayed ultrasound as a feasible alternative to conventional thermal processing of BFP.